Demographics and anthropometrics impact benefits of health intervention: data from the Reduce Obesity and Diabetes Project. (16th January 2019) - Ostrowski, L.; Speiser, P. W.; Accacha, S.; Altshuler, L.; Fennoy, I.; Lowell, B.; Rapaport, R.; Rosenfeld, W.; Shelov, S. P.; Ten, S.; Rosenbaum, M.; ,
Summary: Objective: To determine the efficacy of a 4‐month school‐based health, nutrition and exercise intervention on body fatness and examine possible effects of demographic and anthropometric covariates. Methods: Height, weight, waist circumference and body composition were measured in a diverse population of 644 NYC middle school students (mean ± SD age 12.7 ± 0.9 years; 46% male; 38% Hispanic, 17% East Asian, 15% South Asian, 13.5% African American, 8.5% Caucasian, 8% other) during the fall and spring semesters. Year 1 participants ( n = 322) were controls. Experimental participants (year 2, n = 469) received a 12‐session classroom‐based health and nutrition educational programme with an optional exercise intervention. Results: Groups were demographically and anthropometrically similar. The intervention resulted in significant reductions in indices of adiposity (ΔBMI z ‐scores [−0.035 ± 0.014; p = 0.01], Δ% body fat [−0.5 ± 0.2; p < 0.0001] and Δwaist circumference [−0.73 ± 0.30 cm; p < 0.0001]). Intervention effects were greater ( p = 0.01) in men (ΔBMI z ‐score = −0.052 ± 0.015) versus women (0.022 ± 0.018), participants who were obese (ΔBMI z ‐score −0.083 ± 0.022 kg m −2 ) versus lean (−0.0097 ± 0.020 kg m −2 ) and South Asians (Δ% body fat −1.03 ± 0.35) versus total (−0.49 ± 0.20%) participants ( p = 0.005). Conclusion: A 4‐month school‐based health intervention was effective in decreasing measures of adiposity in middle school students, particularly in men, participants who were obese and South Asians.